The impact of flavors, health risks, secondhand smoke and prices on young adults’ cigarette and e‐cigarette choices: a discrete choice experiment - Buckell, J; Sindelar, J (Wiley, 2019)
Aims To estimate young adults’ preferences for cigarettes and e‐cigarettes, and how preferences vary by policy‐relevant factors. A related aim was to provide information on potential substitution/complementarity across cigarettes and e‐cigarettes ahead of policy selection. Design An online discrete choice experiment (DCE) in which respondents chose their preferred option among cigarettes, two types of e‐cigarettes (disposable/reusable) and ‘none’. Each cigarette‐type was characterized by policy‐relevant attributes: flavors, short‐term health risks to self, secondhand smoke risks and price. A latent class model identified smoking types that respond differently to these. Setting US tobacco market. Participants A total of 2003 young adults (aged 18–22 years) who ever tried either cigarettes or e‐cigarettes, recruited via the survey platform Qualtrics, matched to the 2015 National Health Interview Survey by age, gender, education and census region. Measurements Respondents’ DCE choices. Findings Young adults fell into two broad categories. One latent group, termed ‘prefer smoking group’, preferred cigarettes and another, ‘prefer vaping group’, preferred e‐cigarettes. The ‘prefer smoking group’ preferred lower prices and lower health harms more than other attributes. The ‘prefer vaping group’ valued these, although price less intensely, and valued health and fruit/candy flavors more. Conclusion Banning all flavors in cigarettes and e‐cigarettes might improve the health of young adults who ever tried either cigarettes or e‐cigarettes. Young adult ever‐triers might be deterred from smoking by increasing cigarette prices and encouraged to switch to e‐cigarettes by reducing the health harms of e‐cigarettes. Reducing health harms of e‐cigarettes could also make the ‘prefer vaping group’ less likely to quit, resulting in increased health harm.